Role playing game for student to learn Malaysian history / Muhammad Azmierul Mazelan - Mazelan, Muhammad Azmierul (2015)
History can change the future. History is important to avoid bad things repeat. However, the history of Homeland Malaysia is more easily forgotten among the younger generation. Secondary school students often fail in the examination. Why do they happen? Between the failures of students this is because students don't understand the events of history, therefore it is difficult to remember. The objective of this project is to test role playing game among students. Through the refresher, students will better understand the events of history. This is because the project is reaching out to students with the concept of role playing game games. Therefore, students are more interested in playing the game and repeat the study subjects of history. In addition, the role playing game is a game that is able to experience as an event that really happened. The project is using the RAD methodology. This project provides an average of 70 percent from the 50 percent it passed increased by 20 per cent of students who passed their exams. Therefore, it is clear that games are also able to assist students to succeed in their examination.